Democracy, Elections, And Populism in Indonesia from The Perspective of Friedrich Nietzsche's Existentialism - William Wihardjo; Supriyadi; Susianto (Universitas Muhammadiyah Palu, 2025)
Article history: This research aims to analyze how populism weakens democratic practices in Indonesia and formulate solutions to keep democracy healthy. With Friedrich Nietzsche's existentialism perspective, this research highlights the importance of individual freedom and responsibility in choosing qualified leaders. The research uses a legal method with a legislative and philosophical approach. The results show that Indonesian democracy, which is synonymous with the division of power between the executive, legislative, and judicial branches, is often distorted by the influence of populism. Elections held every five years to elect people's representatives and executive leaders at various levels are often used by political elites for their interests by exploiting people's emotions through rhetoric and identity politics. This condition is rooted in the criteria for nominating leaders in Law No. 7/2017, which opens space for the emergence of populism and obscures the purpose of democracy “of the people, by the people, and for the people”. To overcome this, the research recommends revising the regulation by adding competency criteria based on the State Civil Apparatus (ASN) merit system for prospective executive leaders. This strategy is a practical implementation of existentialism in legal politics to maintain the quality of democracy while strengthening political education for the community.